Resilience with Employee Job Insecurity During the Pandemic at PT X - Vanessa Christianawati; Sutarto Wijono (Journal of Social Research, 2023)
This study aims to determine the relationship between resilience and job insecurity during the pandemic at PT X. Participants in this study were PT X employees with a population of 805 participants. The method used in this study is correlational quantitative research, with simple random sampling techniques and from the slovin formula has been determined by taking a sample of 89 participants. Resilience measurement uses Connor-Davidson – Resilience Scale (CD-RISC) with Cronbach alpha of 0.938, while to measure job insecurity using Job Insecurity-Scale (JI-S) with Cronbach alpha of 0.940. The scale was distributed in the form of questionnaires, with data analysis using IBM SPSS Statistics version 22 with the Spearman correlation test. The results of data analysis obtained correlation coefficient r = 0.562 with a significance value of 0.000 (p < 0.05), showed that the results obtained were significantly positive, which means there is a significant positive correlation between resilience and job insecurity. The higher the resilience, the higher the job insecurity, and vice versa.